Eksplorasi Alat Musik Angklung Terhadap Konsep Tabung - Simamora, Rona Marisa; Tambunan, Hardi; Simanjuntak, Ruth Mayasari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research uses a qualitative approach with exploratory research type. The study was conducted in class IX of SMP Santo Mikael Indramayu with a sample of 30 students to integrate the concept of mathematical three-dimensional shapes through the exploration of the traditional musical instrument angklung. The research instruments used included observation sheets to record student activities and interactions, and interview guides to explore the responses of students and teachers to exploration-based learning. The data obtained were analyzed using qualitative descriptive analysis techniques, namely by reducing the data, presenting the data in narrative form, and drawing conclusions. The measurement data was used to calculate the surface area and volume of the cylinder, while also observing the relationship between the size of the cylinder and the notes produced. The results show that tubes with large diameter and height produce low tones, while smaller sizes produce high tones. This contextual approach based on ethnomathematics enhances student engagement, understanding of concepts, and critical thinking skills. Learning becomes more meaningful as mathematics is seen as a part of daily life and culture, in line with contextual learning theory and ethnomathematics.